2018
DOI: 10.1016/j.ejmech.2018.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based lead optimization to improve antiviral potency and ADMET properties of phenyl-1H-pyrrole-carboxamide entry inhibitors targeted to HIV-1 gp120

Abstract: We are continuing our concerted effort to optimize our first lead entry antagonist, NBD-11021, which targets the Phe43 cavity of the HIV-1 envelope glycoprotein gp120, to improve antiviral potency and ADMET properties. In this report, we present a structure-based approach that helped us to generate working hypotheses to modify further a recently reported advanced lead entry antagonist, NBD-14107, which showed significant improvement in antiviral potency when tested in a single-cycle assay against a large panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 66 publications
0
76
0
Order By: Relevance
“…When we attempted to introduce the 1,3-benzodioxole moiety in the oxalamide-containing NBD-14108 and NBD-14109, the antiviral activity was completely lost, unlike what was observed by Ohashi et al [7a] . We attempted to replace the 1,3-benzodioxole moiety with its bioisostere, 2,1,3-benzothiadiazole [5] .…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…When we attempted to introduce the 1,3-benzodioxole moiety in the oxalamide-containing NBD-14108 and NBD-14109, the antiviral activity was completely lost, unlike what was observed by Ohashi et al [7a] . We attempted to replace the 1,3-benzodioxole moiety with its bioisostere, 2,1,3-benzothiadiazole [5] .…”
Section: Resultsmentioning
confidence: 69%
“…Previously, we reported that some specific amino acid substitutions in the CD4‐binding site of the ENV gp120 rendered the mutant virus resistant to the NBD compounds, but S375H, S375W, and S375Y mutant viruses were not . In this study, we tested NBD‐14110 against the mutant pseudovirus HIV‐1 HXB2 carrying amino acid substitution S375Y or S375W in the ENV gp120 region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations